The system to analyze of stability of robust steganographic algorithms - Андрущенко, Дмитрий Михайлович (Eastern-European Journal of Enterprise Technologies, 2013)
When building steganographic system for copyright protection, two requirements are presented to the algorithms. First of all, robustness requirement is presented: the resistance level of the data embedded into image to intentional or unintentional container distortion. Second, the requirement of minimal visible container changes when embedding data into an image. These requirements contradict one another; this is due to the fact that the smaller is value of distortion included into image while information imbedding, the less built-in data capability will be. Almost all the algorithms proposed allow to vary resistance parameters and the amount of included changes by changing a so-called embedding force coefficient P. Besides this, the data capability depends on format, size, and image palette, as well as on types and degree of distortion (attacks), to which the image may be exposed. Therefore, a compromise is needed between these two parameters for constructing a reliable and effective steganographic system. This paper describes the software solution developed for a practical evaluation of the stability of steganographic methods for hiding information in digital images. The results received allow us, when creating the system of steganographic data embedding into digital images, to reasonably choose the most appropriate methods and parameters of algorithms that provide the needed capability level to certain container distortions simultaneously with possible "invisibility" of embedded messages. Implementation of the most appropriate methods and parameters of algorithm obtained with the help of system developed into information security area will improve the existing steganographic systems efficiency.